The Anti-Glioma Effect of Juglone Derivatives through ROS Generation - Zhang, Jinsen; Fu, Minjie; Wu, Jinfeng; Fan, Fengfeng; Zhang, Xin; Li, Chunjie; Yang, Hui; Wu, Yonghe; Yin, Yiming; Hua, Wei (Frontiers in Pharmacology, 2022)
Juglone has been extensively reported as a natural antitumor pigment. However, it was easy to be oxidized due to active hydroxy in the quinone. Here, we designed some new juglone derivatives, as the hydroxy was replaced by methyl (D1), allyl (D2), butyl (D3), and benzyl (D4) groups. Nuclear magnetic resonance spectra and mass spectra were applied to test the derivatives and oxidative products of juglone. U87 and U251 cell lines were used for tests in vitro, and primary human GBM cells were applied for in vivo experiments. The cell proliferation and viability by CCK8 and EdU assay demonstrated the inhibition by all 4 derivatives, and IC50 for U87 were 3.99 μM, 3.28 μM, 7.60 μM, and 11.84 μM, respectively. In U251, IC50 were 7.00 μM, 5.43 μM, 8.64 μM, and 18.05 μM, respectively. D2 and D3 were further selected, and flow cytometry showed that apoptosis rates were increased after D2 or D3 treatment via ROS generation. Potential targets were predicted by network pharmacology analysis, most of which were associated with apoptosis, cell cycle, and metabolism pathway. CDC25B and DUSP were two of the most likely candidates for targets. The orthotopic glioblastoma model was established to evaluate the anti-glioma effect and side-effect of juglone derivatives, and the in vivo experiments confirmed the anti-glioma effects of juglone derivatives. In conclusion, new derivatives of juglone were created via chemical group substitution and could inhibit glioma cell viability and proliferation and induce apoptosis rate via ROS generation.